(untitled) (Indian Journal of Nematology, 2024)
Mixed cropping systems of Kerala involve perennial crops viz., coconut, arecanut, coffee, betelvine, cardamom, black pepper, ginger and turmeric in the same piece of land. Plant parasitic nematodes cause significant damage in coconut-based cropping systems leading to reduced yield and economic loss. Under ‘safe to eat’ policy of the state, chemical nematicides are not allowed, because a significant quantity of the spices produced are intended for export to foreign countries and some are consumed in raw state without being processed. The application of chemical pesticides for nematode management will have an adverse effect on soil microflora and fauna, resulting in high levels of pesticide residues in harvested produce. It is, therefore, imperative to implement a bio-intensive nematode management strategy using resistant varieties, alternating crops, planting antagonistic crops, and incorporating biofortified organic manures. The selection of nematode-tolerant domesticated or wild species and the incorporation of resistance through breeding offer an eco-friendly alternative to chemical nematicides. Fungal and bacterial antagonists have been proven effective against root-knot nematodes in mixed cropping systems in Kerala. Application of organic manures, mulching and growing antagonistic crops helps to reduce nematode population and improve soil health in mixed cropping systems involving plantation crops. Integrated management programmes are to be formulated in multi-crop production systems based upon the impact of the control method on nematode population and benefit-cost ratio as the level of control varies with environmental factors, crop and targeted nematode.